Etiology, Comorbidities, and Health Service Use in a Clinical Cohort of Children With Hearing Loss. Issue 6 (29th July 2022) - Olivier, Nadia; Shepherd, Daisy A.; Smith, Libby; Carew, Peter; Paxton, Georgia A.; Downie, Lilian; Rose, Elizabeth; Dawes, Kathryn; Sung, Valerie
Abstract : Objective: To examine etiology, comorbidities, and health service use in a cohort of children with permanent hearing loss. Receiving an etiological diagnosis can inform reproductive planning, rehabilitation outcomes, predict additional disabilities, and direct intervention or management decisions. Design: Retrospective audit of 518 deaf/hard-of-hearing children attending a tertiary pediatric outpatient clinic (2016–2019) using descriptive statistics. We used linear regression to investigate the relationship between degree of hearing loss, comorbidities, and health service use. Results: Of the 518 children who attended the clinic, 481 (92.9%) proceeded with testing for etiology. Most children (399/518, 77.0%) were diagnosed with hearing loss by 3 mo of age. Of the children tested, the cause of hearing loss was confirmed in 234/481 (48.6%), suspected in 113/481 (23.5%), and unknown in 134/481 (27.9%); 17/341 (5.0%) had congenital cytomegalovirus (CMV), 17/320 (5.3%) had enlarged vestibular aqueducts, 67/213 (31.5%) of children with bilateral hearing loss had connexin mutation, and 25/72 (34.7%) of children with unilateral loss had hypoplastic/absent cochlear nerve on imaging. The odds of having a definitive/suspected diagnosis were twice as likely for indivduals with profound hearing loss than mild hearing loss (OR 2.1; 95% CI, 1.2–3.9; P = 0.02). The majority (348/518, 67.2%) of children had medical comorbidities, and most children attended otolaryngology (453/518, 87.5%), early intervention (358/518, 69.1%), and genetic (287/518, 55.4%) services. Conclusions: Children with hearing loss have diverse etiologies, most have comorbidities, and attend multiple services. Most families elected to proceed with diagnostic testing for etiology. Current guidelines and expanded access to genetic testing identified a confirmed/suspected etiological diagnosis in 72.1% of children tested. The number of comorbidities correlated with service use, regardless of hearing loss severity.